2021
DOI: 10.1002/ece3.7184
|View full text |Cite
|
Sign up to set email alerts
|

Soil physicochemical properties drive the variation in soil microbial communities along a forest successional series in a degraded wetland in northeastern China

Abstract: The Sanjiang Plain is the biggest freshwater wetland locating in northeastern China. Due to climate change and human activities, that wetland has degraded to a successional gradient from the original flooded wetland to dry shrub vegetation and a forest area with lower ground water level, which may result in changes in soil microbiologic structure and functions. The present study investigated the microbial diversity and community structure in relation to soil properties along that successional gradient. The soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 69 publications
0
31
0
Order By: Relevance
“…In addition, the differences in the composition of aboveground vegetation in our study led to differences in the growth and metabolism of plant roots and the composition and quality of aboveground litter. In turn, this changed the content and physicochemical properties of organic nutrients in the soil, resulting in variations in the soil microorganisms (Deng, Zhang, et al, 2019; Sui et al, 2021). According to the comprehensive NMDS analysis in our study, coniferous forest (LG) and mixed forest (LGQM) belonged to one category, whereas broadleaved forests (BD and BP) belonged to another (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the differences in the composition of aboveground vegetation in our study led to differences in the growth and metabolism of plant roots and the composition and quality of aboveground litter. In turn, this changed the content and physicochemical properties of organic nutrients in the soil, resulting in variations in the soil microorganisms (Deng, Zhang, et al, 2019; Sui et al, 2021). According to the comprehensive NMDS analysis in our study, coniferous forest (LG) and mixed forest (LGQM) belonged to one category, whereas broadleaved forests (BD and BP) belonged to another (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…According to the comprehensive NMDS analysis in our study, coniferous forest (LG) and mixed forest (LGQM) belonged to one category, whereas broadleaved forests (BD and BP) belonged to another (Figure 1). The α diversity of soil bacteria in the coniferous forest was higher than in the broadleaved forests and broadleaved and coniferous mixed forests, which may be due to the relationship between soil bacterial diversity and forest age and developmental stage (Sui et al, 2021). Larix gmelinii constitutes the original and current dominant community in the study area and its ecological stability is high, whereas other forests were mainly formed after logging activities.…”
Section: Discussionmentioning
confidence: 99%
“…The physicochemical environment also regulates the supply of water, oxygen, nutrients, and other resources, which are necessary for microbial communities to use SOC, as well as for plant C assimilation and deposition as detritus or rhizodeposits (Luo et al, 2021). The stabilization of OC in soil has been shown to vary significantly because of physical stabilization mechanism, chemical stabilization mechanism, and biochemical protection mechanism (Feng et al, 2013; Sui et al, 2021). However, large field data sets showing spatial heterogeneity of edaphic variables in coastal wetlands remain scarce, which perpetuates the extensive uncertainties about the patterns of SOC stocks and the main controlling factors.…”
Section: Introductionmentioning
confidence: 99%
“…Soil physicochemical properties have a great influence on bacterial community composition [ 7 , 50 , 64 , 65 ]. Our findings indicated that the different soil management practices of RF and MC farming systems cause a significant difference in soil physicochemical properties, resulting in the different composition of soil bacterial communities and their metabolic functions ( Figure 5 and Table 3 ).…”
Section: Discussionmentioning
confidence: 99%